Pengaruh Latihan Defense Defense Drills Terhadap Hasil Receive Smash dalam Olahraga Bola Voli pada Atlet Klub Bintang Muda Kec. Bandar Sribawono - Ferdi Zulkarnain; Anggun Tri Astuti; Tri Alim Saputra Hidayat; Bambang Ariyanto; Misrodin Misrodin (Peneliti.net, 2022)
The purpose of this study was to determine the effect of defense drills on training the results of receive smash in volleyball in Bintang Muda club athletes, Bandar Sribawono district. this research is using experimental method. The design used in this research is ordinal pairing per-test, post-test design. The population in this study were female volleyball athletes at the Bintang Muda club. The sampling technique in this study used total sampling. The instrument in this study used a receive smash test result. The results and conclusions in this study are that there is a significant effect of defense drills training on the receive smash results of Bintang Mas female athletes. where the receive smash results increase after doing defense drills